The role of bisphenol A and its analogues as endocrine disruptors influencing the thyroid gland: a short review (Journal of Medical Science, 2020)
Bisphenols (BPs) are common plastic additives widely used in industry, hence, human exposure to BPs is inevitable. The best known BP is bisphenol A (BPA), the production of which and its analogues has been increasing worldwide. This chemical is classified as an endocrine-disrupting chemical, inferring with hormonal homeostasis. Indeed, BPA is associated with the development of oestrogen-dependent neoplasms, infertility, metabolic disorders and neurobehavioral disturbances. However, there is a lack of evidence regarding the impact of BPA and its analogues on the thyroid, with most studies mainly performed on animals or in vitro. This review aims to summarise the knowledge regarding the relationship between BPA and its analogues on the thyroid gland.